Sliding mode control for altitude and attitude stabilization of quadrotor UAV with external disturbance - A Noordin; M A M Basri; Z Mohamed (IAES Indonesian Section, 2019)
This paper addresses the problem of robust altitude and attitude control of ‘×’ mode configuration quadrotor UAV using Lyapunov stability based sliding mode control with saturation function. The dynamic model of the quadrotor was derived by considering nonlinearity factor. MATLAB Simulink was used to simulate the model in two different conditions; without and with the presence of external disturbance. This was done to test the robustness of the control method. Simulation results showed that the sliding mode controller provides good performance and robustness against disturbance.